Protective Effect of SIRT1 Activator on the Knee With Osteoarthritis - Zhou, Zhenquan; Deng, Zhenhan; Liu, Yuwei; Zheng, Yizi; Yang, Shiwei; Lu, Wei; Xiao, Deming; Zhu, Weimin (Frontiers in Physiology, 2021)
Osteoarthritis (OA) is one of the most common chronic musculoskeletal disorders, which is correlated with aging. SIRT1 activator, resveratrol, acts as crucial regulator on aging, may have potential therapeutic effect on osteoarthritis. Rabbit OA model was established by destabilized medial meniscus (DMM) surgery. A total of 40 healthy male New Zealand rabbits were divided into five groups: control group (sham operation), OA group, low dose (LD), middle dose (MD) and high dose (HD) resveratrol treated OA groups. Six weeks after operation, 0.8 ml normal saline was injected into the knee joints in the control and OA groups every other day. 0.8 ml of 5, 10 and 15μmol /L resveratrol were injected to the knee joints in LD, MD and HD groups every other day, respectively. Rabbits were sacrificed 2 weeks after medication. The articular cartilage of the knee joint was collected for micro CT, histology and Western blot analysis. Obvious articular cartilage lesion and joint space narrowing was detected in the OA group. Compared with the OA group, less osteoarthritic changes were seen in MD and HG groups. MD and HG groups had significantly lower bone volume fraction (BV/TV), trabecular number (Tb.N) and Mankin scores than LD and OA groups (p<0.05). There wasn’t significant difference between the OA and LD groups (p>0.05). Expressions of SIRT1 and p53 detected by western blot were also consistent with the aforementioned conclusion. Therefore, resveratrol can activate SIRT1 gene to play a protective role in OA process by inhibiting chondrocyte apoptosis, trabecular bone number increasing of the subchondral bone, as well as elevation of bone density. It demonstrated the importance of the SIRT1 in maintaining articular cartilage health and provides a promising therapeutic intervention in the treatment of OA.